2021
DOI: 10.1093/neuros/nyab300
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predictors of Revision Lumbar Fusion Outcomes and the Impact of Spine Surgeon Variability: Does It Matter Whether the Primary Surgeon Revises?

Abstract: BACKGROUND There is a paucity of information regarding treatment strategies and variables affecting outcomes of revision lumbar fusions. OBJECTIVE To evaluate the influence of primary vs different surgeon on functional outcomes of revisions. METHODS All elective lumbar fusion revisions, March 2018 to August 2019, were retrospectively categorized as performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
3
2
Order By: Relevance
“…15 A recent retrospective study evaluated the impact of a different surgeon on outcomes after revision spine fusion identifying a greater 6month ODI improvement among patients operated on by a different surgeon. 26 In contrast, our study found no significant differences across any PROM regardless of whether the index surgeon or a different surgeon performed the revision. However, we did identify that patient's operated on at a different hospital than their index fusion did not report improvement in baseline physical or mental health.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…15 A recent retrospective study evaluated the impact of a different surgeon on outcomes after revision spine fusion identifying a greater 6month ODI improvement among patients operated on by a different surgeon. 26 In contrast, our study found no significant differences across any PROM regardless of whether the index surgeon or a different surgeon performed the revision. However, we did identify that patient's operated on at a different hospital than their index fusion did not report improvement in baseline physical or mental health.…”
Section: Discussioncontrasting
confidence: 82%
“…Patients undergoing revision surgery are more likely to experience only modest improvement in disability and physical function postoperatively 15 . A recent retrospective study evaluated the impact of a different surgeon on outcomes after revision spine fusion identifying a greater 6-month ODI improvement among patients operated on by a different surgeon 26 . In contrast, our study found no significant differences across any PROM regardless of whether the index surgeon or a different surgeon performed the revision.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Yet, it is important to highlight that the average ΔODI improvement across our cohort at three months and one year post-revision was 13.36 and 18.66, respectively. In comparison, previous reports have documented mean ODI improvements of 6.58, and 5.0 at 6 months following revision lumbar fusion [24,25]. Similarly, Djurasovic et al highlighted a modest improvement in ODI by 11.4 points in comparison to significantly greater improvements in patients undergoing primary lumbar fusion [7].…”
Section: Resultsmentioning
confidence: 74%